Holder Solvability of Quasi-Linear Parabolic Systems in the Divergent Form - Mykola Yaremenko (Pan-American Journal of Mathematics)
In this article, we consider a quasilinear parabolic system under fair general conditions with form-boundary conditions on the singular coefficients. We establish the requirements on the structural coefficients of the parabolic system under which the quasilinear system has the unique solution in the Holder functional space.